Trade and Development Report 2009 - Conference des Nations Unies sur le commerce et le développement (United Nations, 2010)
The Trade and Development Report 2009, subtitled Responding to the Global Crisis - Climate Change Mitigation and Development” addresses the main issues of global economic outlook and short-term policy response to the financial and economic crisis, international monetary reform to complement stricter financial regulation and climate change mitigation as a process of structural change. The report analyzes global economic prospects within the framework of the current economic and financial crisis. It also heeds the short-term fiscal, financial and monetary policies that were adopted in response to the impacts of the 2008-2009 crisis. It also looks at the question of how increased efforts aimed at climate change mitigation can be combined with forward-looking development strategies and rapid growth in developing countries.